2016
DOI: 10.1016/j.ijpharm.2016.09.088
|View full text |Cite
|
Sign up to set email alerts
|

Reevaluation of the diametral compression test for tablets using the flattened disc geometry

Abstract: Mechanical strength is an important critical quality attribute for tablets. It is classically measured, in the pharmaceutical field, using the diametral compression test. Nevertheless, due to small contact area between the tablet and the platens, some authors suggested that during the test, the failure could occur in tension away from the center which would invalidate the test and the calculation of the tensile strength. In this study, the flattened disc geometry was used as an alternative to avoid contact pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…Furthermore, several studies indicate that the interpretation of the results of the Brazilian test are not always straightforward [11,12]. In a previous study, we demonstrated that the use of cylindrical tablets did not make it possible to ensure a central failure during the diametral compression test [13]. The use of a flattened geometry ( Fig.…”
Section: Introductionmentioning
confidence: 90%
See 2 more Smart Citations
“…Furthermore, several studies indicate that the interpretation of the results of the Brazilian test are not always straightforward [11,12]. In a previous study, we demonstrated that the use of cylindrical tablets did not make it possible to ensure a central failure during the diametral compression test [13]. The use of a flattened geometry ( Fig.…”
Section: Introductionmentioning
confidence: 90%
“…In our case symmetrical compaction was used. Two different sets of flat-faced euro B punches were used (ACM, Avilly-Saint-Leonard, France) as already described elsewhere [13]. The first set was round with a diameter of 11 mm.…”
Section: Compressionmentioning
confidence: 99%
See 1 more Smart Citation
“…The largest number of the presented studies (35.6% of the total) deal with the stress/density distribution within the tablet during compression [ 5 , 15 , 27 , 61 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 ]. From these, 31.3% deal with the effect of punch shape [ 61 , 74 , 79 , 82 , 85 ].…”
Section: Application Of Fea Modelling For Pharmaceutical Tabletsmentioning
confidence: 99%
“…By applying FEM, we can understand the physical behaviors of a complex object and predict the performance of a design such as the tableting process [2][3][4][5] and strength simulation. [6][7][8] The response surface method (RSM) is used to model the relationships between design variables and pharmaceutical responses. 9,10) A nonlinear RSM incorporating thin-plate spline interpolation (RSM-S) has been developed to determine the acceptable formulations of pharmaceutical compounds.…”
mentioning
confidence: 99%